Development and validation of the screening tool for identifying elder abuse by caregivers (STIEAC) - Oludoyinmola Omobolade Ojifinni; Obioma C. Uchendu (PLoS ONE, 2026)
Purpose Elder abuse is a global concern, yet detection methods focus mainly on victims. In community settings, trusted caregivers may perpetrate abuse that remains hidden due to cultural norms. Existing tools lack a contextual fit for sub-Saharan Africa. This study developed and validated the Screening Tool for Identifying Elder Abuse by Caregivers (STIEAC) in Southwest Nigeria. Methods The study used Artino’s seven-step questionnaire development framework, combining a literature review and caregiver focus groups to create culturally relevant items across the neglect, physical, psychological, financial, and sexual abuse domains. Expert panels ensured content and face validity, followed by pilot testing after which the revised tool was administered in a survey among 1119 caregivers. The psychometric evaluation included factor analysis, reliability (Cronbach’s alpha, Guttman split-half), and construct validity via correlations with the Zarit Burden, General Health Questionnaire-12, and Katz Activities of Daily Living scales. Results The STIEAC’s 10-item structure encompasses the five elder abuse domains, demonstrating high internal consistency (Cronbach’s α = 0.90) and reliability (split-half coefficient = 0.713). Bartlett’s test was significant (χ² = 7642.08, p < 0.001), and the KMO measure was adequate (0.896). Domain-specific reliability was highest for neglect (α = 0.87) and lowest for sexual abuse (α = 0.03). Construct validity was supported by a positive correlation with the ZBI (r = 0.294, p = 0.001) and negative correlations with the GHQ-12 (r = −0.349, p = 0.001) and the Katz ADL (r = −0.160, p = 0.001). Conclusion The STIEAC is a reliable 10-item tool reflecting culturally nuanced elder abuse perpetration by caregivers in community settings. Despite the low consistency of the sexual abuse subscale, it has strong overall validity, filling a critical gap for screening for elder abuse in sub-Saharan Africa and assisting researchers and practitioners.